2008
DOI: 10.1016/j.socscimed.2007.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Widowhood and mortality among the elderly: The modifying role of neighborhood concentration of widowed individuals

Abstract: The effect of death of a spouse on the mortality of the survivor (the "widowhood effect") is wellestablished. We investigated how the effect of widowhood on mortality depends on the neighborhood concentration of widowed individuals in the United States. We developed a large, nationally representative, and longitudinal dataset from Medicare claims and other data sources characterizing 200,000 elderly couples, with nine years of follow-up (1993-2002), and estimated multilevel grouped discrete-time hazard models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 57 publications
(59 reference statements)
1
42
0
Order By: Relevance
“…It is likely that networks do not always adapt to a loss and network-level recovery might not translate into recovery at the individual level; notably, we were not able to evaluate both connective recovery and the subjective experience of loss here. Evidence on recovery among widows, for example, suggests that social support from friends does not often compensate for the loss of a spouse 28 and that recovery may depend on a shared loss, as widowed individuals fare better when they live close to others who have experienced the death of a spouse 29 . Furthermore, the apparently smooth trajectories of network recovery seen here might correspond to noisier oscillations in recovery at the individual level 30 .…”
Section: Nature Human Behaviourmentioning
confidence: 99%
“…It is likely that networks do not always adapt to a loss and network-level recovery might not translate into recovery at the individual level; notably, we were not able to evaluate both connective recovery and the subjective experience of loss here. Evidence on recovery among widows, for example, suggests that social support from friends does not often compensate for the loss of a spouse 28 and that recovery may depend on a shared loss, as widowed individuals fare better when they live close to others who have experienced the death of a spouse 29 . Furthermore, the apparently smooth trajectories of network recovery seen here might correspond to noisier oscillations in recovery at the individual level 30 .…”
Section: Nature Human Behaviourmentioning
confidence: 99%
“…A recent US study found that widows/widowers living in neighbourhoods with low population proportions of widows/widowers had a 22% increased mortality risk among men and 17% among women compared to the married, while the increased mortality risk was 17% among men and 15% among women in neighbourhoods with high proportions of widows/widowers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of individual marital status were as expected (Roelfs et al, 2011;Shor et al, 2012). Only a few studies have estimated effects of the family structure in the community on health, health behaviour or mortality (Kravdal, 2007;Thorlindson et al, 2012), or considered the importance of family structure as a conditioning variable (Burrows et al, 2011;Huijts and Kraaykamp, 2011;Subramanian et al, 2008). In our data, a high proportion divorced was linked to high mortality (in the absence of the controls for constant unobserved municipality factors that were included in the earlier Norwegian study by Kravdal, 2007).…”
Section: A Few Comments On the Effects Of Individual And Aggregate Somentioning
confidence: 60%